2018
DOI: 10.1042/bcj20180399
|View full text |Cite
|
Sign up to set email alerts
|

A copper transcription factor, AfMac1, regulates both iron and copper homeostasis in the opportunistic fungal pathogen Aspergillus fumigatus

Abstract: Although iron and copper are co-ordinately regulated in living cells, the homeostatic effects of each of these metals on the other remain unknown. Here, we show the function of AfMac1, a transcriptional activator of the copper and iron regulons of , on the interaction between iron and copper. In addition to the copper-specific AfMac1-binding motif 5'-TGT-3' found in the promoter region of , the iron-specific AfMac1-binding motif 5'-(C/G)NN(A/T)(A/C)-3' was identified in the iron regulon but not in the copper r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…1). It has recently been reported that AfMacA also regulates iron homeostasis and its localization in the cell varies depending on copper and iron concentration (Park et al 2018). AfmacA disruption generated a copper starvation phenotype with manifest growth defects in copper depletion conditions (Cai et al 2017;Kusuya et al 2017;Park et al 2017).…”
Section: Genetic Regulation Of Copper Homeostasismentioning
confidence: 99%
“…1). It has recently been reported that AfMacA also regulates iron homeostasis and its localization in the cell varies depending on copper and iron concentration (Park et al 2018). AfmacA disruption generated a copper starvation phenotype with manifest growth defects in copper depletion conditions (Cai et al 2017;Kusuya et al 2017;Park et al 2017).…”
Section: Genetic Regulation Of Copper Homeostasismentioning
confidence: 99%
“…Zinc is an essential trace element and performs various physiological functions in living cells. Previously, we found that copper regulates iron metabolism [ 40 ], and in this report, we sought to understand the interaction between zinc and copper metabolism. To investigate the effect of zinc on copper metabolism in A. fumigatus , the effect of zinc on growth of the Δafmac1 strain was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported that iron and copper interact functionally in A. fumigatus and that copper regulates iron metabolism, and vice versa [ 40 , 41 ]. We observed that iron regulates the expression of genes related to copper metabolism, and another group reported that iron and zinc functionally interact with one another.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Copper has historically been used to control fungal and bacterial growth in healthcare settings (Casey et al., 2010; Lazary et al., 2014). It has become apparent that hosts use copper to fight A. fumigatus infection, and A. fumigatus has also evolved some mechanisms to resist copper-mediated toxicity by regulating copper homeostasis (Kusuya et al., 2017; Wiemann et al., 2017; Cai et al., 2018; Park et al., 2018). Thus, copper plays an important role at the host– A. fumigatus axis, and a detailed understanding of copper homeostasis regulation in A. fumigatus can lead to new strategies for antifungal drug development.…”
Section: Introductionmentioning
confidence: 99%